(untitled) (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to examine the demand dynamics for water sports on Lake Eğirdir and winter sports at Davraz Ski Center within the scope of recreational sports tourism from a multi-stakeholder perspective. The study comprehensively addresses the dimensions that influence sports tourism demand, including capacity and season management, safety, pricing and packaging, events and collaborations, environmental sustainability, marketing, and data-driven decision-making. The research was designed using a qualitative research approach and employed a multi-site case study design. The study group consisted of representatives from the municipality and provincial tourism directorate, facility operators, sports clubs and coaches, tourist guides, and civil society organization representatives. Data were collected using a semi-structured interview guide consisting of a core and modular structure and analyzed using thematic and content analysis methods. The research findings reveal that the demand for sports tourism is highly seasonal and dependent on climatic conditions, and that the short season at Davraz Ski Center limits the sustainability of demand. While capacity overload and congestion problems occur during peak periods, demand remains low during shoulder seasons. It was determined that security measures are provided at a basic level, but crisis management and coordination between stakeholders need to be strengthened. The fact that pricing processes are largely determined by public institutions and federations limits dynamic pricing and targeted packaging applications. Although races, festivals, and sports camps have a strong demand-boosting effect, it has been observed that these events are not planned within a sustainable calendar. It has been determined that environmental sustainability practices are not standardized and are not systematically communicated to visitors. While social media and influencer-based promotion stand out in marketing activities, data-driven decision-making and CRM applications have been found to be limited. Consequently, it was concluded that in order to increase demand in a sustainable manner in the sports tourism destinations of Eğirdir and Davraz, short-term pricing and campaign applications must be integrated with medium and long-term infrastructure investments, a four-season sports tourism vision, and a data-driven, multi-stakeholder management approach.